Interactions between callose and cellulose revealed through the analysis of biopolymer mixtures - Radwa H. Abou-Saleh (Nature Portfolio, 2018)
Despite their importance in plant development and defence the properties of (1,3)-β-glucan remain largely unknown. Here, the authors find that addition of (1,3)-β-glucans increases the flexibility of cellulose and its resilience to high strain, an effect originating in molecular level interactions.